Railway maintenance reservation scheduling considering detouring delays and maintenance demand. (March 2023) - Buurman, B.; Gkiotsalitis, K.; van Berkum, E.C.
Abstract: Railway maintenance works are performed to reduce the probability of the occurrence of a failure on the components of the railway infrastructure. The scheduling of maintenance work is important in supporting the normal daily operation of the railway. By proper maintenance scheduling, operational hindrance in terms of extra travel costs due to detouring can be minimized. In addition, contractors can be given more space to execute maintenance activities with more flexibility. This study aims to optimize the maintenance schedules for both train operators and maintenance contractors by considering hindrance and flexibility for both stakeholders, respectively. This study tries to achieve this by modeling important factors contributing to both objectives and relevant constraints in a multi-objective optimization problem. The methods presented for solving the multi-objective model are the ɛ -constraint method and NSGA-II. Two path finding algorithms are modified to consider train travel limitations and are used to support the solutions methods. Both solution strategies are initially tested on fictive networks to analyze the performance. In a case study, the Dutch railway network is assessed and used to create new maintenance schedules based on the new model. Highlights: Multi-objective optimization model for railway maintenance reservation scheduling. Consideration of maintenance demand and detouring delays with two path finding algorithms. Problem-tailored ɛ -constraint and NSGA-II solution methods. Analysis in toy networks and the Dutch railway network.